Many Asias but One Singapore: The Problematics of Creative Industry - SINGH, Kirpal (Institutional Knowledge at Singapore Management University, 2013)
The author discusses issues concerning the creative industry in Singapore. He highlights a National Conversation event which features the critical role and position of the creative industry in Lion City aiming to be a global hub for the arts and culture. He also highlights the Singapore Day celebration as well as the country's relationship with the other Asian countries.